2021
DOI: 10.22354/in.v26i2.1018
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion envenomation in Brazil: an update

Abstract: Accidents caused by scorpions represent a major health problem on planet, both in individual terms and in the public health sphere. Morbid events can occur in different manifestations, and different clinical conditions must be differentiated for adequate treatment. In addition to the potential injury to human hosts, scorpion venom has been investigated for the therapy of several illnesses. Based on these aspects, the present article aims to present the clinical, diagnostic, therapeutic and prophylactic aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Seventy percent of our patients were hyponatremic & hypokalemia was discovered in 62% of our patients. This is in agreement with previous researches revealed that hyponatremia and hypokalemia occur most frequently [21].…”
Section: Discussionsupporting
confidence: 94%
“…Seventy percent of our patients were hyponatremic & hypokalemia was discovered in 62% of our patients. This is in agreement with previous researches revealed that hyponatremia and hypokalemia occur most frequently [21].…”
Section: Discussionsupporting
confidence: 94%
“…Accidents caused by scorpions are common in the southeastern region of Brazil, particularly in the state of São Paulo, due to the significant increase in scorpions in urban habitats . There are four families of scorpions in Brazil (Buthidae, Bothriuridae, Chactidae and Hormuridae), and the genus Tityus, belonging to the Buthidae family, is the most responsible for serious accidents (PARRELA et al, 2022). The species Tityus serrulatus (popularly known as the yellow scorpion) and Tityus bahiensis (known as the brown or black scorpion) are common in the southeastern region of Brazil and are responsible for a large number of accidents and deaths in the country (BUCARETCHI et al, 2014;AMADO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%